2022
DOI: 10.1111/ecc.13648
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy‐induced peripheral neuropathy onset is associated with early risk of depression and anxiety in breast cancer survivors

Abstract: Objective: The objective was to assess for an association between chemotherapyinduced peripheral neuropathy (CIPN) onset and development of depression and anxiety in breast cancer (BrCa) survivors. Methods: A retrospective observational cohort was used and identified from Optum's De-identified Clinformatics ® Data Mart Database years 2012-2015. Three groups of women were derived based on BrCa and CIPN status: BrCa+/CIPN+ (n = 244), BrCa+/CIPNÀ (n = 8870), and BrCaÀ/CIPNÀ (n = 1,125,711). The ratio of the preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 32 publications
1
12
0
2
Order By: Relevance
“…Regarding depressive symptoms, it has been reported that up to 25%–30% of women with breast cancer report these symptoms at some point since diagnosis [ 59 , 60 ], and identifying a set of factors that are linked to depression in patients with early-stage breast cancer on adjuvant treatment is challenging. The risk of depression may be associated with the cancer, also with the severity of the disease, with the treatment itself (due to its adverse effects, as is the case of depression associated with peripheral neuropathy induced by adjuvant chemotherapy [ 28 , 61 , 62 ]). We detected an increase in the percentage of patients with relevant burden of depressive symptoms increased under AROi treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding depressive symptoms, it has been reported that up to 25%–30% of women with breast cancer report these symptoms at some point since diagnosis [ 59 , 60 ], and identifying a set of factors that are linked to depression in patients with early-stage breast cancer on adjuvant treatment is challenging. The risk of depression may be associated with the cancer, also with the severity of the disease, with the treatment itself (due to its adverse effects, as is the case of depression associated with peripheral neuropathy induced by adjuvant chemotherapy [ 28 , 61 , 62 ]). We detected an increase in the percentage of patients with relevant burden of depressive symptoms increased under AROi treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For the management of neuropathic pain from CIPN, ASCO recommends using duloxetine because it has the best evidence in the CIPN population 19 . Additionally, duloxetine may be a good choice for patients who also have concomitant depression or anxiety or both 23 . After duloxetine, treatment is similar to other painful neuropathies, including tricyclic antidepressants, serotonin norepinephrine reuptake inhibitors (SNRIs), and gabapentinoids.…”
Section: Chemotherapy-induced Peripheral Neuropathymentioning
confidence: 99%
“…21 Early recognition and management of CIPN are critical because CIPN is associated with acute and chronic impairments in physical and psychological function; increased risk for falls, fractures, and disability; and a decreased quality of life. [22][23][24][25] CIPN affects not only individual cancer survivors but the whole health system; compared with cancer-and chemotherapy-matched controls, health care for patients with CIPN costs $20,000 per year more than health care for cancer survivors without CIPN. 26 Improved recognition and management of CIPN is critical given the increasing population of cancer survivors, now totaling more than 18.5 million in the United States, many of whom received neurotoxic chemotherapy.…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations